2019
DOI: 10.1186/s12885-019-5721-2
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the EQ-5D-5 L in family caregivers of leukemia patients

Abstract: Purpose This study aimed to test the validity and reliability of the five-level EuroQol five-dimensional (EQ-5D-5 L) instrument in family caregivers (FCs) of leukemia patients in Heilongjiang of China. Methods A cross-sectional survey was conducted on 298 family caregivers (FCs) of leukemia patients from three major cancer centers in the capital city of Heilongjiang province of China. Their dimensional scores of the EQ-5D-5 L were compared with those of the WHOQOL-BREF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…All 5 aspects were calculated to an index score with the maximum of 1.000 [39]. An intraclass correlation coefficient of 0.987 for the EQ-5D index score, and a significant correlation with WHOQOL-BREF were noted [40]. The study sample showed that Cronbach's alpha was 0.723.…”
Section: Eq-5dmentioning
confidence: 99%
“…All 5 aspects were calculated to an index score with the maximum of 1.000 [39]. An intraclass correlation coefficient of 0.987 for the EQ-5D index score, and a significant correlation with WHOQOL-BREF were noted [40]. The study sample showed that Cronbach's alpha was 0.723.…”
Section: Eq-5dmentioning
confidence: 99%
“…An English study examined the test-retest reliability of the EQ-5D-3L in the UK general population and reported an ICC of 0.83 in the EQ-Index scores [16]. A Chinese study of carers of cancer patients reported high test-retest reliability for EQ-VAS and EQ-Index scores of 0.87 and 0.99 respectively [17]. However, the follow-up between test and retest in that particular study was only 1 day meaning the results were likely to be heavily influenced by recall bias compared with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a health economics context, the retrospective assessment of health status, gathered for the purpose of estimating healthy life expectancy has been shown to closely approximate estimates based on prospective health information [14]. Numerous studies have investigated the test-retest reliability of the EQ-5D [15][16][17][18][19][20] and other studies have supported the use of retrospective measurement of baseline data following a health event or an intervention [21][22][23], and retrospective measurement in preference to using population norms in determining baseline health status [24,25]. However, the validity of the retrospective use of the EQ-5D has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with its predecessor the EQ-5D-3L, the increased level of alternative answers generated less ceiling and floor effects and higher reliability and sensitivity [29]. This study adopted the validated Chinese version of the EQ-5D-5L [30]. An EQ-5Dutility index was calculated for each respondent using the value set (ranging from -0.39-1.00, "worse than death" to 1 "absence of problems") recently developed in China [31].…”
Section: Measurements and Variablesmentioning
confidence: 99%